Desirable Information Technology Competencies for Government Employees in Thailand 4.0 Era - Nuansomsri, Chuleekorn; Jantavongso, Suttisak (Princess of Naradhiwas University Journal, 2020)
The objectives of this research were: 1) to synthesize the desirable Information Technology (IT) competency framework of work performance of government employees in Thailand 4.0 era and 2) to study the desirable IT competencies for employees from the perspectives of executives. The questionnaires were used to collect data. The target group was 323 executives working in government organizations. Data were analyzed using basic statistics: means and standard deviation. The results revealed the desirable IT competency framework for government employees in Thailand 4.0 era consisted of 8 components and 40 variables. From the perspectives of executives, the desirable IT competencies consisted of 5 components and 20 variables in which the competency in Technology had the highest mean.